1997
DOI: 10.1016/s0014-5793(97)01502-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and spectral properties of DNA miniduplexes with the terminal G·A mispairs and 3′ or 5′ dangling bases

Abstract: The tetradeoxyribonucleotide pAGCG in 1 M NaCl forms duplexes with terminal non-canonical pAWG pairs with stability significantly exceeding that for the duplex (pAGCT) P and lower than that for the duplex (pCGCG) P . The deoxyriboduplex (pAGCG) P is considerably stabilized by 3P-Y and slightly by 5P-X dangling bases. Therefore, the stability of duplexes with 3P dangling bases decreases in the order (pAGCGY) P s (pCGCGA) P s (pAGCTA) P . The sum of the independent stabilizing effect of the of 5P-pG and 3P-A dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Absorbance at 260, 270, and 300 nm was measured. Absorbance at 300 nm was used as a baseline and was subtracted from the two other denaturation curves [ 50 ]. The melting temperature (Tm) of RNAs was calculated as the maxima of the first derivative of absorbance on temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Absorbance at 260, 270, and 300 nm was measured. Absorbance at 300 nm was used as a baseline and was subtracted from the two other denaturation curves [ 50 ]. The melting temperature (Tm) of RNAs was calculated as the maxima of the first derivative of absorbance on temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of the value of the free energy of this nick is likely to be a lower limit since it has been determined relative to a gap complex that has a 3'A-A sequence adjacent to the duplex component under study. It is known that single strand 3' overhangs of this type can stabilise an adjoining duplex (26)(27)(28). In particular, it has been shown that a 3'A-A overhang adjacent to a C base on an adjoining duplex, similar to that employed in this study exhibits a stabilisation contribution of -0.5 kcal/mol (29).…”
Section: Discussionmentioning
confidence: 67%
“…The optical data were collected every 0.2°C. Thermodynamic parameters of the duplex formation (changes of enthalpy Δ H °, entropy Δ S ° and Gibbs free energy at 37°C, Δ G ° 37 ) were obtained by direct non-linear fitting and concentration methods ( 31 ). Fitting of the melting curves were performed using a two-state model corrected for intramolecular hairpin formation as described ( 32 ).…”
Section: Methodsmentioning
confidence: 99%